Mechanical and thermal properties of polylactic acid filled lignin powder biocomposite filaments with epoxidized palm oil for sustainable 3d printing application - Abd Rahman, Nurul Amirah; Anuar, Hazleen; Mohd. Nordin, Nurfarahin; Mohd Asri, Syazeven Effatin Azma; Ali, Fathilah; Suhr, Jonghwan (Persatuan Saintis Muslim Malaysia (PERINTIS), 2021)
Initiative have been taken to study the effect of lignin powder and epoxidized alm oil (EPO) on polylactic acid (PLA). Since lignin is a very abundant by product with a cheap cost, using it in any value-added application would result in a significant economic benefit. EPO is a well-known plasticizer in polymer studies and the addition effect of EPO into this composite is look upon. The aim of this study is to fabricate polylactic acid (PLA) filled with lignin powder and EPO biocomposite filaments for 3D printing application based on the fused deposition modelling (FDM) process. The renewability property of the PLA has been the main consideration as sustainable approach in this work. Nonetheless, the high brittleness of PLA had limited its fitness especially in the application that requires higher strength, hence the addition of lignin as reinforcements have been implemented in this study to overcome this problem. The lignin has been extracted from the oil palm empty fruit bunches (OPEFB) fiber via alkaline extraction process and was added at different weight percent into PLA using thermal extrusion. Epoxidized palm oil (EPO) was also added at a constant weight percent for all filaments. The mechanical, thermal, and functional characterizations of the filaments have been done and compared with the neat PLA. The mechanical properties had shown the optimized properties comes from PLAE1, where addition of EPO had reduced the brittleness of PLA. Thermal studies conducted on these filaments also shows excellent thermal stability of PLAE1 with higher degradation temperature other than good miscibility of PLA and lignin.